The Influence of Leadership Style on Teacher Performance Through Human Resource Development at Integrated Islamic Elementary Schools in Depok City - Bayinah, Ika Iqomatul; Yunizar; Joeliaty (International Journal of Science and Society, 2024)
This study aims to analyze the influence of leadership styles on teacher performance through human resource development. The method used includes the formation of regression models and path analysis, utilizing SPSS tools. The sample was selected using random sampling techniques, referring to the theory by Hair et al., with a sample size ratio of 1:5 from the parameters measured. There are 36 indicators being examined, resulting in a total sample size of 180. The study results indicate a direct influence of leadership styles on teacher performance at 0.613 and an indirect influence at 0.664, meaning the indirect influence is greater than the direct influence. This leads to the conclusion that, indirectly, leadership styles significantly affect teacher performance through human resource development. Meanwhile, the percentage contribution of the influence of leadership styles on teacher performance through human resource development is 54,8%.